Prediksi Potensi Relawan Pendonor Darah Menjadi Pendonor Darah Tetap dengan Penerapan Metode Klasifikasi Decision Tree - Afifah Cahayani Adha; Y Yuhandri; Gunadi Widi Nurcahyo (Jurnal Informasi dan Teknologi, 2021)
Blood donation is an important activity to obtain blood as a raw material into the blood supply chain. If there is not enough blood in the human body, then human survival will be threatened, for some conditions blood transfusions are required, such as accidents, childbirth or certain grades of dengue fever. UTD PMI Pekanbaru City is the organizing body for blood donation activities in the process of helping and serving the blood needs for public. Based on data from the Ministry of Health in 2019, Pekanbaru City lacked in blood stock 32.4 percent, which the ideal supply of blood bags in Pekanbaru City was 130,019 blood stock. This causes some hospitals difficult to find the supply of blood stock. The cause of lacking in blood bags' availability in Pekanbaru City was the number of volunteer donors fluctuates and the public's low interest in becoming volunteer blood donors. So it becomes a problem when the number of requests for blood increases, while the supply at the blood bank is running low. The method used in this research was the Decision Tree method. The algorithm used in this study was the C.45 Algorithm. To solve the problems that occur, data analysis of blood donor volunteers was carried out. Based on the results of the testing data analysis as many as 50 records, 6 rules were produced which can be concluded that age over 19 years with an entrepreneur job has the potential to become a permanent blood donor